2022
DOI: 10.3390/ijerph192214716
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Microbiome in Women Infected with HPV16 and High-Risk HPVs

Abstract: Human papillomavirus type 16 (HPV16) and/or high-risk (Hr-) HPV are the main causes of cervical cancer. Another element that may contribute to the development of cervical cancer is the microbiota. To date, no study has investigated the entire cervical microbiome, which consists of bacteria, fungi, and viruses. In this study, cervical samples with different histopathology (CIN1, CIN2, and CIN3), with or without HPV16 and Hr-HPVs infection, were enrolled. From bacterial community analysis, 115 bacterial species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 56 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…For example, L. crispatus turned out to be the predominant Lactobacillus species in women with normocenosis for the ASCUS and LSIL groups, while L. iners prevailed in the HSIL group. There are contradictions in the works of other authors concerning L. iners: some studies show that it accompanies HPV infection and SIL (Wang et al, 2019;Sasivimolrattana et al, 2022;Xu et al, 2022), whereas other studies demonstrate no association of the kind (McKee et al, 2020;Gomez Cherey et al, 2023;Ivanov et al, 2023). L. crispatus is considered to protect from SIL progressing in HPV (Cheng et al, 2020), since it produces a lot of the D-isomer of lactic acid which increases the viscosity of the vaginal secrete and elevates its ability to sequester virions, in contrast to L. iners which produces only the L-isomer (Kalia et al, 2020;Nicolò et al, 2023).…”
Section: Discussionmentioning
confidence: 87%
“…For example, L. crispatus turned out to be the predominant Lactobacillus species in women with normocenosis for the ASCUS and LSIL groups, while L. iners prevailed in the HSIL group. There are contradictions in the works of other authors concerning L. iners: some studies show that it accompanies HPV infection and SIL (Wang et al, 2019;Sasivimolrattana et al, 2022;Xu et al, 2022), whereas other studies demonstrate no association of the kind (McKee et al, 2020;Gomez Cherey et al, 2023;Ivanov et al, 2023). L. crispatus is considered to protect from SIL progressing in HPV (Cheng et al, 2020), since it produces a lot of the D-isomer of lactic acid which increases the viscosity of the vaginal secrete and elevates its ability to sequester virions, in contrast to L. iners which produces only the L-isomer (Kalia et al, 2020;Nicolò et al, 2023).…”
Section: Discussionmentioning
confidence: 87%
“…Based on the analyzed literature (Table 1), significant differences were observed in the cervicovaginal microbiome between the HPV-positive and HPV-negative women. Generally, a wider variety of bacterial species was observed in the HPV-positive women, primarily due to the abundance of species other than Lactobacillus and a shift towards anaerobic bacteria [31,36,41,111,117,130,133,[135][136][137]139,143]. The majority of the studies indicated that HPV-negative women had a normal cervical microbiota characterized by the abundance of Lactobacillus.…”
Section: Decrease: Hpv+hsil Groupmentioning
confidence: 99%
“… 16 , 248 , 249 The VMB has been found correlated with the severity of cervical lesions. As cervical lesions advance, VMB diversity escalates, 250 , 251 accompanied by increased abundance of Lactobacillus iners and dysbiosis‐related bacteria such as Porphyromonas , Prevotella , Bacteroides , and Anaerococcus species predominating. 252 , 253 , 254 , 255 HPV infection can also adversely affect the VMB, 96 , 256 and these two factors synergistically drive cervical lesions progression.…”
Section: Hpv and Its Pathogenesismentioning
confidence: 99%